Conduct against circumferential resections of the cervical trachea: experimental study - Crestanello, Francisco A; Gómez Fossati, Carlos; Melognio, Silvio; Fossati, Enrique (Cirugía del Uruguay, 2020)
Several reconstruction procedures after tubular resections of the trachea at cervical level are reviewed. Experimental reconstruction by anastomosis of tlie remaining ends, with intercartilaginous sutures in short and long resections and the reconstruction by grafts (hono or self) in short tubular resections are evaluated. After short resections the results with anastomosis are good, and bad after long resections. The value of the suture tension, mobilization of the remaining ends and the points used are evaluated. Considerations about the causes of the constant bad results with grafts are made.